Cognitive functioning and soccer heading: one-year longitudinal assessment among professional players - Palma, Giovanni Batista; Lima, Mariana Drummond Martins; Rodrigues, Ana Carolina Oliveira; Friedlaender, Clarisse Vasconcelos; Azevedo Filho, Celso Furtado de; Lasmar, Rodrigo Campos Pace; Caramelli, Paulo (Arquivos de Neuro-Psiquiatria, 2025)
Background Soccer is the most popular sport worldwide, and the only one in which players purposely and repetitively use their head to hit the ball. In recent years, more attention has been given to subconcussive impacts, which are characterized by a cranial impact that does not result in known or diagnosed concussion on clinical grounds.Objective To investigate the effects of soccer heading on cognitive functioning among professional soccer players.Methods In a longitudinal case-control study, 22 professional soccer players were compared with 37 non-athletes on 2 occasions (T0 and T1) separated by a 1-year interval. The cognitive assessment consisted of computerized neuropsychological tests and the Brief Neuropsychological Assessment Battery (NEUPSILIN).Results There was no evidence of cognitive impairment among athletes, who actually outperformed the controls in terms of score, accuracy, and reaction time in certain tests. Moreover, the estimates of heading exposure did not correlate with the cognitive performance of players. The intragroup analyses revealed that while the controls improved their performance on three cognitive variables from T0 to T1, no improvement occurred among players. However, within-group variation in performance from T0 to T1 was similar.Conclusion Although the present study has not shown an association between soccer heading and cognitive impairment, subconcussive impacts may have a negative effect on brain function, as improvement in cognitive performance was not observed among athletes. Future and longer longitudinal investigations are needed to clarify the relationship between soccer heading and cognition.
Keywords: Cognition; Neurology; Athletes; Soccer; Brain Injuries, Traumatic